2019
DOI: 10.1038/s41550-019-0883-z
|View full text |Cite
|
Sign up to set email alerts
|

Transition from eyeball to snowball driven by sea-ice drift on tidally locked terrestrial planets

Abstract: Tidally locked terrestrial planets around low-mass stars are the prime targets for future atmospheric characterizations of potentially habitable systems 1 , especially the three nearby ones-Proxima b 2 , TRAPPIST-1e 3 , and LHS 1140b 4 . Previous studies suggest that if these planets have surface ocean they would be in an eyeball-like climate state 5-10 : ice-free in the vicinity of the substellar point and ice-covered in the rest regions. However, an important component of the climate system-sea ice dynamics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 83 publications
2
36
0
Order By: Relevance
“…The habitable-zone planet LHS 1140 b is now known to contain a significant amount of water with a relatively high probability. Previous works have studied the actual state of water layers on the surface of this planet by analyzing the possible eyeball, lobster, or snowball scenarios (Yang et al 2020). Future atmospheric studies with the James Webb Space Telescope and extremely large telescopes will be able to distinguish among these scenarios.…”
Section: Discussionmentioning
confidence: 99%
“…The habitable-zone planet LHS 1140 b is now known to contain a significant amount of water with a relatively high probability. Previous works have studied the actual state of water layers on the surface of this planet by analyzing the possible eyeball, lobster, or snowball scenarios (Yang et al 2020). Future atmospheric studies with the James Webb Space Telescope and extremely large telescopes will be able to distinguish among these scenarios.…”
Section: Discussionmentioning
confidence: 99%
“…Assuming an Earth-like atmosphere with updated sea-ice paramerization the 3D model study of Yang et al (2020) suggested a reduced surface ocean on LHS 1140 b (from 12% to 3% surface coverage). Diamond-Lowe et al (2020) observed two transits of LHS 1140 b with the twin Magellan Telescopes but their analysis suggested that a precision increased by a factor of about 4 was needed for the detection of e.g.…”
Section: Introductionmentioning
confidence: 99%
“…SGW interactions with sea ice, particularly in the Arctic Ocean, are an important mechanism within large‐scale climate variability and change on Earth (Squire, 2020). Moreover, sea‐ice dynamics have been shown to be of great significance for ocean‐covered exoplanet climate (Yang et al., 2020). Unfortunately, the simulations presented do not have the sea‐ice model dynamically coupled to the SGW model.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Moreover, sea-ice dynamics have been shown to be of great significance for ocean-covered exoplanet climate (Yang et al, 2020). Unfortunately, the simulations presented do not have the…”
Section: Accepted Articlementioning
confidence: 96%
See 1 more Smart Citation